Mengukur Kepuasan Wisatawan Nusantara di Daya Tarik Wisata Pura Luhur Uluwatu Kabupaten Badung Bali - Hutapea , Moga Yuda; Susila, I Made Gede Darma; Ariesta , I Putu Agus Suarsana (Fakultas Bisnis dan Pariwisata, 2024)
Tourist attraction of Uluwatu Temple is one of the cultural attractions that has high value and history as well as diversity of other uniqueness. This tourist attraction has a role in bringing the number of domestic and foreign tourist visits to the island of Bali, especially Badung Regency. This study aims to determine influence between tourist attractions and service quality on domestic tourist satisfaction in Puru Luhur Uluwatu Tourist Attraction. This study used a quantitative descriptive approach to measure traveller satisfaction. This study used research data collection techniques in the form of field observation, interviews, documentation and questionnaires. In this study using 100 respondents as the number of samples in his research with an accidental sampling approach. Then the data will be analyzed descriptively qualitatively and using multiple regression analysis using SPSS version 26. The results of this study found that tourist attractions partially have a positive and significant effect on tourist satisfaction, service quality partially has a positive and significant effect on tourist satisfaction at Pura Luhur Uluwatu Tourism Attraction, tourist attractions and service quality simultaneously have a positive and significant effect on tourist satisfaction at Pura Luhur Uluwatu Tourism Attraction. This means that these two have an impact on the satisfaction of domestic tourists who visit, so managers need to improve their products and services. The next research recommendation is to conduct further research to measure tourist satisfaction based on variables that were not used in this study.